Egg Production and Physical Quality in Cortunix cortunix japonica Fed Diet Containing Piperine as Phytogenic Feed Additive - M. Hilmi; . Sumiati; D. A. Astuti (Faculty of Animal Science, Bogor Agricultural University, 2015)
The objective of this study was to determine the effect of piperine as a phytogenic feed additive on quail performances and egg quality. The experiment used a completely randomized design with five treatments and four replications and used ten quails with one week of age in each replication. The piperine was added to the diets at concentrations of 0 (T0), 15 (T1), 30 (T2), 45 (T3), and 60 mg/kg body weight (T4) for 8 consecutive weeks. The results showed that addition of 60 mg/kg body weight (T4) of piperine significantly (P<0.05) reduced feed consumption, egg production, egg mass, income over feed cost (IOFC), and increased water consumption as compared to the other treatments. The addition of 15-60 mg piperine/kg body weight significantly (P<0.05) reduced eggshell weight and increased egg yolk color score. The conclusion of this experiment was that the addition of piperine at 15-45 mg/kg body weight could be used as phytogenic feed additive to improve performance, IOFC, haugh unit, and yolk color.Key words: egg, feed additive, phytogenic, piperine, quail